Factors Influencing the Decision to Choose a Place of Work in Hanoi, Vietnam - Duc Tai Do; Manh Dung Tran; Thi Ngoc Lan Nguyen (International Journal of Small and Medium Enterprises and Business Sustainability, 2019)
This research was conducted to investigate the impact of factors that influence the decisions of graduated students to choose workplaces in Hanoi, Vietnam. Data were collected through interviews with 245 graduated students from the Department of Accounting from the University of Labor and Social Affairs, Hanoi, Vietnam. With this data, we have used Cronbach's Alpha, EFA and a regression model to determine the level of impact of independent variables on the dependent variable, i.e. the decision to choose a workplace. The results showed that the determinants included the work environment factors in Hanoi (WEFs) and the personal factors of graduates (PFs) which both have positive relationships with the decision to choose a workplace in Hanoi. Based on this finding, this paper gives several recommendations for both graduated students as well as relevant government institutions in response to employee requests in Hanoi for students graduating in Accounting.